Bacteriophages as Biocontrol Agent in Food Safety - Yarn Wai, Ga; Yew Huat Tang, John; Radu, Son (International Journal of Engineering and Technology, 2018)
Food contamination with pathogens has been continual and significant problem worldwide. These pathogens causes foodborne diseases that lead to deleterious effect to the health of consumer and the financial losses to food manufacturer. The emergence of foodborne pathogen isÂ  further complicated with the infection from multiple antibiotic resistance food pathogens and the formation of biofilm on food processing equipment as well as utensils that cause the process of decontamination become more challenging. Bacteriophage is recognized for its effectiveness as biocontrol against food pathogen and relatively harmless to man. Bacteriophage can be applied at any point of the food chain such as phage therapy of livestock, biosanitizer (disinfectant) in the food processing environment, and biocontrol (additives) of food products. Bacteriophage is an obligate parasite of bacterial and due to its host specificity and binding capability, bacteriophage appear as a more advantageous decontamination agent compared to other chemical intervention which might introduce chemical hazard. Various studies have shown the effectiveness of bacteriophage in combating food-borne pathogens and insignificant risk of development bacteriophage resistant bacteria. However the efficacy of the bacteriophages varies depending on the source of isolation, the type of food, surface materials and food matrixes. Thus, it is noteworthy to get the insight of current microbiological hazard in food and the potential use of bacteriophages as biocontrol agent.Â Â